SELECTIVE ANTICANCER ACTIVITY OF CURCUMA XANTHORRHIZA FERMENTED JUICES - Ruksiriwanich, Warintorn; Akazawa, Hiroyuki; Jantrawut, Pensak (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to investigate the anticancer activity and toxicity of fermented juices from six Thai plants, Garcinia mangostana Linn., Tinospora crispa Linn., Litchi chinensis Sonn., Dimocarpus longan Lour., Curcuma xanthorrhiza (CX) Roxb., and Averrhoa bilimbi Linn., in normal cells as compared with common commercial fermented juices. Methods: The plants were fermented for 3 months, and their biological activities including 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) scavenging, metal chelating, lipid peroxidation inhibition, and tyrosinase inhibition activities were subsequently evaluated. Furthermore, their in vitro anticancer activities in human colon adenocarcinoma (HT-29), cervical cancer (HeLa), hepatocellular carcinoma (HepG2), and murine melanoma (B16F10) cell lines and their toxicities in normal human skin fibroblasts were assessed. Results: The fermented juice of CX showed a higher antioxidant activity than those of the other plants, with an SC50 (DPPH scavenging) value of 0.011 mg/mL, an IPC50 (lipid peroxidation inhibition) of 0.027 mg/mL, an MC50 (metal chelating) value of 0.170 mg/mL, and an IC50 (tyrosinase inhibition) of 0.027 mg/mL. Moreover, the fermented juice of CX displayed selective toxicity in cancer cell lines (HeLa, HepG2, and B16F10), with a significantly lower toxicity in normal human skin fibroblasts as compared with an expensive commercial fermented juice product. Conclusion: The present study suggests that the fermented juice of CX can be developed as a functional food supplement with antioxidant properties or as an anticancer product with low toxicity to normal human skin fibroblasts.